Implikasi Hukum Wanprestasi Pemerintah pada Kontrak Pembangunan Pasar Ranggulalo: Analisis Putusan Nomor 28/Pdt.G/2021/PN Dgl - Lo, Adeline; Lee, Elena Philomena; Chen, Natasya Edgina; Baretta, Nicole; Nugraha, Dwi Putra; Tanaya, Velliana (SIGn Jurnal Hukum, 2025)
Government Default in Construction Contracts executed under assistance task projects raises questions concerning accountability and legal certainty, as exemplified by the Ranggulalo Market construction case. This study aims to analyze the legal implications of the Sigi Regency Government’s Default and to identify how legal accountability for the outstanding contract payment was determined based on Decision Number 28/Pdt.G/2021/PN Dgl. A normative legal research methodology utilized case, statutory, and conceptual approaches through qualitative analysis of the court decision, pertinent regulations, and secondary legal materials. The analysis reveals that the court determined the Defendant had committed Default and was responsible for paying the outstanding contract balance—acknowledging the involvement of the Co-Defendant—despite complexities concerning the Commitment-Making Official’s mandate, predicated on the binding civil law nature of the contractual relationship. The principal legal implications arising from this Default include the imposition of direct financial obligations on the government, the disruption of the fundamental principle of contractual equilibrium, diminished legal certainty for service providers, and the emergence of administrative and institutional consequences for the regional government involved. In conclusion, this judgment affirms government accountability in civil contracts and underscores the judiciary’s vital role in upholding the pacta sunt servanda principle. Concurrently, it highlights the urgent need to refine regulations concerning assistance tasks and strengthen contract governance within regional government environments.